2016
DOI: 10.1136/bjsports-2016-096154
|View full text |Cite
|
Sign up to set email alerts
|

Association of psychological variables and outcome in tendinopathy: a systematic review

Abstract: The association of psychological variables and outcome in tendinopathy: a systematic review ABSTRACT Objective: Fear, anxiety, depression, distress and catastrophisation are all factors known to affect pain and disability levels. To date, the association of such psychological factors has yet to be established in tendinopathy. Therefore, the purpose of this paper was to determine if psychological variables are associated with tendinopathy and whether any such variables may be associated with pain and disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 63 publications
3
70
0
2
Order By: Relevance
“…Participants were required to be a minimum of 18 years old, have access to the internet, an available email address, proficient with written and spoken English, and identified as having AT as determined by the attending physiotherapist according to established criteria (Adrian Mallows, Debenham, Walker, & Littlewood, ; Martin et al, ): Local Achilles tendon pain reproduced with load‐based activity, for example heel raising, for at least ten days duration Tenderness on palpation of the Achilles tendon Range of movement at the ankle within normal limits To minimize confounding variables for recovery, participants presenting post‐operatively, or with lumbar spine related disorders which may refer directly to the Achilles tendon region were excluded (Mallows et al, ; Martin et al, ). The exclusion criteria were: Tendon rupture Receiving treatment for post‐surgical recovery Reproduction of pain in the Achilles region on movements of the spine …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were required to be a minimum of 18 years old, have access to the internet, an available email address, proficient with written and spoken English, and identified as having AT as determined by the attending physiotherapist according to established criteria (Adrian Mallows, Debenham, Walker, & Littlewood, ; Martin et al, ): Local Achilles tendon pain reproduced with load‐based activity, for example heel raising, for at least ten days duration Tenderness on palpation of the Achilles tendon Range of movement at the ankle within normal limits To minimize confounding variables for recovery, participants presenting post‐operatively, or with lumbar spine related disorders which may refer directly to the Achilles tendon region were excluded (Mallows et al, ; Martin et al, ). The exclusion criteria were: Tendon rupture Receiving treatment for post‐surgical recovery Reproduction of pain in the Achilles region on movements of the spine …”
Section: Methodsmentioning
confidence: 99%
“…As current strategies appear incomplete, the need to investigate factors beyond the specific effects of exercise on peripheral tissue appears to be one way of potentially optimising outcomes in AT. In recent times, cognitive and contextual influences such as self‐efficacy, working alliance and expectations have been highlighted as potentially relevant factors that would benefit from investigation in tendinopathy (Mallows, Debenham, Malliaras, et al, ; Mallows, Debenham, Walker, & Littlewood, ). Working alliance, also known as ‘therapeutic alliance’ or ‘patient‐therapist relationship’, can be defined as “the working rapport or positive social connection between the patient and the therapist” (Joyce, Ogrodniczuk, Piper, & McCallum, ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher management rates for RCRP were found among patients from most disadvantaged socioeconomic status. A multitude of factors may be associated with RCRP and more prevalent in socioeconomic disadvantaged areas, including rates of metabolic disease and mental health issues such as anxiety and depression [55][56][57]. The higher management rate of RCRP among male GPs than female GPs, identified after adjustment for other GP and patient characteristics, may reflect the higher management rate of musculoskeletal problems (overall) by male GPs in Australia [58,59].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Knowledge of psychological characteristics associated with persistent tendinopathies is scarce and inconsistent 19. In LE, some studies have reported higher levels of anxiety and depression,20 21 whereas others have not 9 10.…”
Section: Introductionmentioning
confidence: 99%